La remise en eau de la plaine de Piolenc-Mornas face à la constitution d’une culture locale de l’arrangement - Marie Anckière; Julien Langumier (VertigO)
The plain of Piolenc-Mornas (Vaucluse) is a former flooded territory by the river Rhône modified by the huge project of hydroelectricity exploitation in the 1970’s. The possibility of making it liable to floods again is studied within a global plan of optimization of floods expansion areas. Following solidarity principle between upstream and downstream, the stakeholders want to use this agricultural area to stock water and limit rise in water level. Trough numerous projects of infrastructures set in this plain in the 1990’s (high speed train), the inhabitants learnt to deal locally with the constraints of global land settlement. They have developed an attitude to claim for compensations which participate to a “bargaining culture”. Towards the stakes in the present, how does the memory of the flooded past of the plain participate to the identity of territory? How the former negotiations relative to the implementation of infrastructures have participated in turning the rural plain into modernity? Finally, how these two dynamics, memory and negotiation, influence the mobilization against the project of optimization of floods expansion areas ?